The Ideal Donor Site Dressing: A Comparison of a Chitosan-Based Gelling Dressing to Traditional Dressings. Issue 3 (17th May 2022) - Uke, Nkemjika; Singh, Simran; Sorensen, Grant E; Frost, Joshua; Venable, Amanda; Burge, Bailey; Terziyski, Ilina; Payberah, Ebrahim; Griswold, John
Abstract: Donor site wound management is critical in split-thickness skin graft surgeries. These sites typically recover in 7 to 14 days due to the dermal-imbedded keratinocytes that promote skin regeneration. An ideal donor site dressing can help to mitigate pain, reduce infection risk, promote hemostasis, and accelerate healing times. Additionally, this dressing would be easy to apply in the operating room, easily managed, and cost-effective. Chitosan-based gelling dressings (CBGD) possess many of these qualities that make an ideal donor site dressing. We conducted a retrospective chart review of patients who received CBGD as part of their postoperative wound care plan. We collected data on infections, hemostasis, dressing failure, and hospital course over a 14-month period where CBGD was used as the donor site dressing. One hundred and fourteen patients were evaluated. We found an infection rate of 7%, a bleed-through rate of 1.8%, and a re-application rate of 9.6%. The average CBGD cost per patient was 75.15. CBGD has acceptable infection rates, and pain scores as traditional donor site dressings. However, it possesses several qualities of a suitable donor site dressing notably swift healing rates, impressive hemostatic property, and low cost. Our study supports the idea that CBGD is a suitable donor site dressing for split-thickness skin graft surgeries.